1997
DOI: 10.1094/pdis.1997.81.7.739
|View full text |Cite
|
Sign up to set email alerts
|

A Model Defining the Relationship Between Temperature and Leaf Wetness Duration, and Infection of Watermelon by Colletotrichum orbiculare

Abstract: Controlled environment experiments were conducted to determine the relationship between temperature, leaf wetness duration, and infection of watermelon by Colletotrichum orbiculare. Flats of watermelon seedlings were inoculated and exposed to various combinations of temperature (12, 15, 18, 21, 24, 27, and 30°C) and leaf wetness duration (2, 4, 8, 12, 16, and 24 h). The experimental design was a split-plot, with whole units represented by temperature and subunits represented by leaf wetness duration. Anthracno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 9 publications
0
23
0
1
Order By: Relevance
“…Similar relationships between temperature and leaf wetness have been well documented for a variety of plants and diseases (Evans et al 1992;Mathieu and Kushalappa 1993;Monroe et al 1997). Although the regression equation developed here applies to the controlled environmental conditions of the present study, it lays the foundation for the development of a model for fungicide spray scheduling under field conditions.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Similar relationships between temperature and leaf wetness have been well documented for a variety of plants and diseases (Evans et al 1992;Mathieu and Kushalappa 1993;Monroe et al 1997). Although the regression equation developed here applies to the controlled environmental conditions of the present study, it lays the foundation for the development of a model for fungicide spray scheduling under field conditions.…”
Section: Discussionmentioning
confidence: 60%
“…There was a large increase in disease development with duration of leaf wetness of 24 h. However, as our study did not look at leafwetness periods beyond 24 h, it was not possible to determine if 24 h was the optimal leaf-wetness period for infection of saskatoon. Similarly, studies of other pathogens (Grove 2002;Monroe et al 1997) and E. mespili on Photinia ×fraseri (Baudoin 1986a) also revealed a pattern of increased disease with increasing leaf wetness. In these studies, a period of 24 h was the longest duration examined.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Thompson and Jenkins (1985) showed that a reduction in lesion area results in a lower number of Colletotrichum lagenarium (Pass.) conidia produced from infected leaves of Cucumis sativus L. Disease-forecasting models based on leaf-wetness duration and temperature (Grove 2002;Monroe et al 1997) can be integrated with a fungicide spray program to help reduce disease. A similar disease-forecasting model based on leafwetness duration and temperature for E. mespili on saskatoon was developed (Holtslag et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Várias combinações de fitopatossistemas seguem este modelo, como a infecção de Stemphylium vesicarium em pêra (MONTESINOS et al, 1995); Alternaria cucumerina em melão rajado (EVANS; NYQUIST; LATIN, 1992); Colletotrichum orbiculare em melancia (Monroe et al, 1997) e Colletotrichum lindemuthianum no feijoeiro (DALLA PRIA, 1997).…”
Section: Ajuste Do Modelo De Superfície De Resposta Da Ramuloseunclassified